Pitfalls in precision stereotactic surgery - Zrinzo, Ludvic (Medknow Publications & Media Pvt Ltd, 2012)
Precision is the ultimate aim of stereotactic technique. Demands on stereotactic precision reach a pinnacle in stereotactic functional neurosurgery. Pitfalls are best avoided by possessing in-depth knowledge of the techniques employed and the equipment used. The engineering principles of arc-centered stereotactic frames maximize surgical precision at the target, irrespective of the surgical trajectory, and provide the greatest degree of surgical precision in current clinical practice. Stereotactic magnetic resonance imaging (MRI) provides a method of visualizing intracranial structures and fiducial markers on the same image without introducing significant errors during an image fusion process. Although image distortion may potentially limit the utility of stereotactic MRI, near-complete distortion correction can be reliably achieved with modern machines. Precision is dependent on minimizing errors at every step of the stereotactic procedure. These steps are considered in turn and include frame application, image acquisition, image manipulation, surgical planning of target and trajectory, patient positioning and the surgical procedure itself. Audit is essential to monitor and improve performance in clinical practice. The level of stereotactic precision is best analyzed by routine postoperative stereotactic MRI. This allows the stereotactic and anatomical location of the intervention to be compared with the anatomy and coordinates of the intended target, avoiding significant image fusion errors.